Contingency Plan: Comparison of Health Policies in Managing COVID-19 in Singapore and Indonesia - Al Khairy Siregar, Khalish Arsy; Chairin Hanifa, Deasy Nur (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2021)
Introduction: Singapore is one of the countries with the lowest mortality rate and the best handling of COVID-19. Singapore can be an example for Indonesia on COVID 19 pandemic handling.Methods: The method used is a literature review from google platform with these keywords: “Singapore Health Policy in COVID-19, Indonesian Health Policy in COVID-19, Singapore's success in suppressing COVID-19”. The analysis was done by comparing the policies taken from the two countries in dealing with COVID-19.Results: Singapore and Indonesia did indeed have very big differences in terms of government and in broad areas, it cannot be denied that Indonesia can have the same opportunity as Singapore in providing a good health disaster mitigation system for the community. Three factors influence Singapore's success in dealing with COVID-19: 1) having a responsive and efficient health disaster mitigation system, 2) government legitimacy which is determined by the capacity of the state. Singapore has a semi-centralized government with high legitimacy the experience of dealing with pandemics in the past, 3) Singapore's experience with SARS in the past makes Singaporeans understand very well the impact of the pandemic on their economic activities and social life.Conclusion: Several things can be emulated from Singapore in handling COVID-19 was the transparency, strong communication between community and the government, prioritizing the benefit and safety of civil society and building obedience and awareness of Covid 19 prevention.